1990
DOI: 10.3171/jns.1990.73.4.0548
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spinal metastases from kidney cancer by presurgical embolization and resection

Abstract: Surgical treatment of bone metastases from kidney cancer is often complicated by profuse blood loss. The authors report the results of a retrospective review of 30 consecutive patients who underwent surgery for spinal metastases from kidney cancer. Seventeen patients (57%) were operated on after failing radiation therapy. Prior to operation, selective spinal angiography and embolization were performed in 17 patients with no permanent neurological deficits resulting. Gross total resection of the tumor and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 23 publications
2
50
0
3
Order By: Relevance
“…Complications include transient or permanent quadriplegia or quadriparesis as well as aortic dissections in up to 8.5 % of patients [19,20]. In our series, there were no local or systemic complications following embolisation.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Complications include transient or permanent quadriplegia or quadriparesis as well as aortic dissections in up to 8.5 % of patients [19,20]. In our series, there were no local or systemic complications following embolisation.…”
Section: Discussionmentioning
confidence: 48%
“…The authors of previous reports have shown efficacy for renal and non-renal spinal metastases such as melanoma, sarcoma, thyroid, breast, prostate, hepatic carcinoma, and neuroendocrine tumours such as paragangliomas [6][7][8][9][10][11][12][13]. Nevertheless, the amount of blood loss is variable [13,[17][18][19][20]. The procedure is associated with minimal morbidity when performed by experienced interventional radiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aspects of vertebral tumor embolization [1,7] and showed the efficacy of preoperative embolization on perioperative blood loss [3,4,10].…”
mentioning
confidence: 99%
“…In addition, some studies have shown that embolisation may cause tumour growth arrest and subsequently pain alleviation and shorter hospital stay [58][59][60]. The timing of the preoperative embolisation is also important.…”
Section: Treatmentmentioning
confidence: 99%